Effects of alcohol on liver apparent diffusion coefficient values: A single center study - Ökçesiz, İzzet; Artas, Hakan; Yalniz, Mehmet (My University, 2021)
Background and Aims: This study aimed to investigate the relationship between liver apparent diffusion coefficient values and potential early-stage liver injury by comparing apparent diffusion coefficient values obtained by liver diffusion-weighted magnetic resonance imaging between individuals with a history of excessive alcohol consumption and healthy volunteers. Materials and Methods: This study enrolled 35 individuals with a history of excessive alcohol consumption and 32 healthy volunteers. In all cases, blood samples were taken to measure biochemical parameters and complete blood count. Upper abdominal magnetic resonance imaging including liver diffusion-weighted imaging was performed. Results: In total, 19 individuals with a history of excessive alcohol consumption and 20 healthy volunteers were included in the study. The mean apparent diffusion coefficient values obtained by high b value (b 1000) diffusion-weighted imaging in individuals with a history of excessive alcohol consumption were lower than those in healthy volunteers. Although no significant difference was observed between the two groups in terms of biochemical parameters, hepatic apparent diffusion coefficient values in both groups were positively correlated with international normalized ratio values and negatively correlated with gamma-glutamyl transferase and alkaline phosphatase levels (r = 0.002, r = ?0.007, r = ?0.049, respectively). Conclusion: Diffusion-weighted imaging is a noninvasive imaging technique that can be used for the detection and follow-up of liver fibrosis induced by alcohol consumption.
Keywords: Genel ve Dahili Tıp; Patoloji; Radyoloji; Nükleer Tıp; Tıbbi Görüntüleme